Giant elastocaloric effect with wide temperature window in an Al-doped nanocrystalline Ti–Ni–Cu shape memory alloy. (15th September 2019) - Chen, Hong; Xiao, Fei; Liang, Xiao; Li, Zhenxing; Li, Zhu; Jin, Xuejun; Fukuda, Takashi
Abstract: Ti–Ni based shape memory alloys are promising elastocaloric materials for solid-state refrigeration. In this paper, we made a comprehensive study on elastocaloric effect of a nanocrystalline Ti–44Ni–5Cu–1Al (at%) alloy exhibiting successive B2–B19–B19′ transformation. The maximum adiabatic temperature decrease by stress removal from 600 MPa is Δ T adi ∼25 K with a small temperature distribution of ∼0.5 K. The value of Δ T adi is consistent with that calculated from strain-temperature relation. The effective working temperature window is ∼55 K, resulting in a high refrigeration capacity of RC = 4.2 kJ/kg. Material coefficient of performance reaches COP ∼9.6 when an Otto cycle is considered. The middle eigenvalue of the transformation matrix is λ2 ∼ 0.99, implying high lattice compatibility between the parent and martensite phases. These properties are related to the diffuse nature of successive B2–B19–B19' martensitic transformation of this alloy. Graphical abstract: Image 1